Can I Manage My Own Classrooms? Perceptions of Rural School Novice Teachers - Yuliandra Yuliandra; Heri Mudra; Hadi Candra (Jurnal Paedagogy, 2026)
This study aims to describe novice teachers’ insights regarding classroom management in rural schools. This Study employed a descriptive method through which the researchers determined a written instrument to be fulfilled. A total of eighty three teachers with various majors (i.e., Math, Biology, English, Physics, Economy, Art, Religion, Counselling, and Sport) were involved in a survey study. Through an online survey, a questionnaire was sent to the participants via email and WhatsApp platform. Collected data were analyzed through a descriptive statistical analysis where means and percentages were used to indicate response estimation. The findings shows that there were eight indicators of rural teachers’ classroom managements, including seating arrangement, student teacher relationship, time management, use of writing board, classroom norms, conducive environment, appropriate instructional techniques, and feedback. From all of them, the teachers encountered barriers in terms of feedback, and use of writing board. It is noticed that novice rural school teachers performed positive attitudes on time management, relationship with students, and norms applied in the classroom. This current study implies that there should be an educational policy that leads the teachers to manage their classrooms as effective as they could.